Simultaneous CSM‐TACE with CalliSpheres® and partial splenic embolization using 8spheres® for hepatocellular carcinoma with hypersplenism: Early prospective multicenter clinical outcome - Zhou, Jun; Feng, Zhuo; Liu, Song; Li, Xiang; Liu, Ying; Gao, Fei; Shen, Jing; Zhang, Yue Wei; Zhao, Guang Sheng; Zhang, Ming (Frontiers in Oncology, 2022)
Background: To prospectively evaluate the efficacy and safety of simultaneous CalliSpheres® microspheres transcatheter arterial chemoembolization (CSM-TACE) and partial splenic embolization (PSE) drug using 8spheres® for hepatocellular carcinoma (HCC) with hypersplenism. Methods: Ninety consecutive HCC patients with hypersplenism who underwent CSM-TACE were selected: 32 patients in CSM-TACE+PSE group, and 58 patients in CSM-TACE group. The peripheral blood cell counts (leukocyte, platelet (PLT), liver function and red blood cell (RBC)), CSM-TACE and/or PSE related complications, and the tumor control rate at 1 month after CSM-TACE were compared. The survival time and prognostic factors were also observed. Results: Before CSM-TACE, there were no significant differences in sex, age, Child-Pugh grade, tumor size, and alpha-fetoprotein (AFP) between the two groups. After CSM-TACE, the PLT and white blood cell (WBC) counts in CSM-TACE+PSE group were significantly higher than those in the CSM-TACE group (P＜0.05). There were no significant differences in RBC before and after treatment (P > 0.05). In the CSM-TACE group, there were no significant differences in WBC, PLT, and RBC before and after treatment (P > 0.05). There was no significant difference in liver function at 1 month after treatment between the two groups. The cholinesterase (CHE) level in the CSM-TACE+PSE group after surgery was obviously higher than that before surgery and higher than that in the CSM-TACE group (P＜0.05). However, the level of CHE returned to the preoperative level 1 month after CSM-TACE in the CSM-TACE group. The objective response rate (ORR) and median overall survival (OS) in the CSM-TACE+PSE group were higher than those in the CSM-TACE group (P＜0.05). The adverse reactions of the two groups were fever, abdominal pain, stomach discomfort, nausea, and vomiting, and no serious complications occurred. The degree of abdominal pain and fever in the experimental group was lower than that in the control group (P > 0.05). Conclusions: Simultaneous CSM-TACE and PSE using domestic embolization particles for HCC with hypersplenism have good safety and efficacy and has a low incidence of PSE-related adverse events, it is conducive to improving liver function reserve, and can further improve the median OS.